GOOD GOVERNANCE IMPLEMENTATION IN REALIZING QUALITY OF PUBLIC SERVICES WITH INTEGRITY - Mohammad Redy; Zainurrafiqi Zainurrafiqi (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2023)
The purpose of this study was to determine the effect of the implementation of good governance on the quality of public services at the Department of Population and Civil Registration of Pamekasan Regency. This research is classified as explanatory research with a quantitative approach. The sample used was 95 respondents with purposive sampling technique. The type of data used is primary data, namely data collection using a questionnaire. Analysis of the data used is Linear Regression with SPSS. The results of this study indicate that the application of good governance has a positive effect on the quality of public services at the Department of Population and Civil Registration of Pamekasan Regency.